Methodology of “14–7” Program: A Longitudinal Follow-Up Study of the Pediatric Population and Their Families Exposed to the Terrorist Attack of Nice on July 14th, 2016 - Morgane Gindt; Morgane Gindt; Susanne Thümmler; Susanne Thümmler; Andréa Soubelet; Andréa Soubelet; Fabian Guenolé; Michèle Battista; Florence Askenazy; Florence Askenazy (Frontiers in Psychiatry, 2019)
Introduction: After a traumatic event, children and adolescents may present several clinical consequences, the most common being Post-Traumatic Stress Disorder (PTSD). Most children and adolescents with PTSD have comorbid disorders, such Attention Deficit Hyperactivity Disorder, depression, attachment and anxiety disorders, sleep disturbances and behavior problems. However, epidemiological studies on the development of PTSD and other psychiatric disorders in children and adolescents as a consequence of a terrorist attack and mass murder are lacking. Long-term follow-up of exposed children and adolescents will help identify risk and protective factors of developing psychiatric and psychological conditions after exposure to traumatic events or situations. The main objective of this article is to present the methodology of “14–7” program. The aim of “14–7” program is to characterize the risk and protective psychosocial factors affecting the clinical evolution of a pediatric population sample, exposed to the terrorist attack of July 14th, 2016 in Nice.Method and Analysis: “14–7” program is a multicentre longitudinal cohort study. Major inclusion criteria are children and adolescents exposed to the terrorist attack and aged under 18 years on July 14th, 2016. These children and adolescents will be compared to a non-exposed to the “14–7” terrorist attack group, matched on age and gender. Participants will be assessed at baseline (T1), 2 years (T2) and 5 years (T3) after the initial assessment (T1), and every 5 years until they are 25 years old. Multiple domains are assessed: 1) mental health disorders, 2) intensity of PTSD symptoms, 3) intensity of comorbid symptoms, 4) quality of the parent–child relationship, 5) intelligence quotient, 6) parental symptoms. We will also establish a biological collection of saliva samples, magnetic resonance imaging (MRI) and actigraphy data collection. Main analyses comprise analyses of variance and regression analyses of predictors of clinical evolution over time.Ethics and Dissemination: The National Ethics Committee “NORD OUEST III” approved the “14–7” Program protocol (number 2017-A02212-51). All patients and their caregivers signed informed consent on enrolment in the “14–7” Program. Inclusions started on November 21st, 2017. Three hundred thirty-five individuals have been included (191 children and adolescents, 144 parents).Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03356028